Why Does the Law of One Price Fail? An Experiment on Index Mutual Funds - Choi, James J.; Laibson, David; Madrian, Brigitte C. (Review of Financial Studies, 2010)
We conduct an experiment to evaluate why individuals invest in high-fee index funds. In our experiments, subjects allocate $10,000 across four S&P 500 index funds and are rewarded for their portfolio's subsequent return. Subjects overwhelmingly fail to minimize fees. We can reject the hypothesis that subjects buy high-fee index funds because of bundled non-portfolio services. Search costs for fees matter, but even when we eliminate these costs, fees are not minimized. Instead, subjects place high weight on annualized returns since inception. Fees paid decrease with financial literacy. Interestingly, subjects who choose high-fee funds sense they are making a mistake.